1995
DOI: 10.1111/j.1439-0523.1995.tb00772.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic improvement in wheat yield and associated traits. A re‐examination of previous results and the latest trends

Abstract: Two field experiments were carried out with seven wheat eultivars (three of them, including a commercial hybrid, released during the last 10 years) representing different eras of plant breeding, to evaluate genetic improvement over the last century in grain yield, height, biomass, harvest index and grain yield eomponents. Plots were fertilized and irrigated, and lodging and diseases were prevented.Main eulm height was negatively correlated with the year of release of the cultivars, probably as a consequenee of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
114
3
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(131 citation statements)
references
References 15 publications
13
114
3
1
Order By: Relevance
“…The results are in accordance with various studies which have revealed the positive impact of increased number of spikes per area on yield [18][19][20][21] and the number of grains per spike [18,22,23]. On the contrary, our results did not confirm studies claiming that higher yields are combined with increased 1000 kernel weight [5,24].…”
Section: Discussioncontrasting
confidence: 45%
“…The results are in accordance with various studies which have revealed the positive impact of increased number of spikes per area on yield [18][19][20][21] and the number of grains per spike [18,22,23]. On the contrary, our results did not confirm studies claiming that higher yields are combined with increased 1000 kernel weight [5,24].…”
Section: Discussioncontrasting
confidence: 45%
“…Grain yield increases during the last century were almost fully (Slafer et al, 1990;Calderini et al, 1999;Fischer, 2007b), or at least mainly (Calderini et al, 1995;Sadras and Lawson, 2011), related to increases in grain number per m 2 . This is in line with the fact that grain growth is frequently sink-limited both in wheat (Jenner, 1979;Savin and Slafer, 1991;Slafer and Savin, 1994;Miralles and Slafer, 1995;Kruk et al, 1997;Borrás et al, 2004;Calderini et al, 2006) and barley (Dreccer et al, 1997;Savin et al, 2006;Bingham et al, 2007).…”
Section: Introductionmentioning
confidence: 98%
“…Por muitos anos, grande parte do aumento da produtividade de trigo esteve associada ao incremento da partição de massa seca para os grãos, enquanto a biomassa da parte aérea não foi modificada (Calderini et al, 1995;Sayre et al, 1997). Em adição, fatores determinantes na produção de biomassa, especialmente a eficiência do uso da radiação, permaneceram praticamente inalterados (Calderini et al, 1997;Fischer et al, 1998).…”
Section: Introductionunclassified